Produção do espaço urbano na Serra do Mel por condomínios fechados em Montes Claros-MG - Luciana Gomes Marques Galvão (2018)
The production and commoditization of urban spaces manifest the logic of monopolist and financial capital, exploited by the real estate market through the creation of new products, revealing a notion of city as a commodity. The production process of the space is expressed by an intense real estate dynamics that is guided by the commoditization of its amenities and environmental assets, raising the exchange value of urban land, and configuring processes of segregation and urban conflicts. This study is based on a perspective of space production and proposes, as an empirical study, the analysis of Serra do Mel in the city of Montes Claros, Minas Gerais, from the perspective of the real estate dynamics that promoted an intense mutation of the landscape, indicating processes of urban restructuring into a course. Thus, the present dissertation aimed to analyze the production of urban space, during the last twelve years (2007-2018), by condominium real estate projects at Serra do Mel in the city of Montes Claros. Specifically, this study aimed to understand the actions from several social agents, the interests that guided their spatial practices, the contradictions involved, the conflicts between them in this production process. Additionally, through these mentioned factors, this research illuminated the real estate dynamics expressed in strategies adopted for urban land valuation by the action of private real estate projects, such as the gated communities at Serra do Mel, in the city of Montes Claros/MG. Therefore, the qualitative approach was chosen, by performing a bibliographical research, documental analysis and field research, including interviews and iconographic. The processes of urban expansion in Montes Claros was intensified in recent years towards the areas that border the urban perimeter, driven by speculative practices and the challenge of creating new markets. In the last twelve years, the west axis of the city was the target of great reconfiguration, forging a new typology of residences, due to the intense construction of gated communities, which was revealed in the space production at Serra do Mel, in Montes Claros, which indicates a process of urban restructuring driven by real estate dynamics. The surveyed condominiums, due to their location at the foothill of the Serra do Mel, reveal a new form of reorganization of the space in Montes Claros, becoming a focus of socio-environmental conflicts before the threat of its irregular appropriation. The new urban typology of housing in closed condominiums results in denial of the city, since this space appropriation is based on individualistic values, of self-sufficiency and pseudo-autonomy of those who are inside the gates, denying access to others. Because inherent to denial, conflict deepens in social relations, by juxtaposing interests, sometimes distorted by contradictory ideologies.